The Escherichia coli Type III Secretion System 2 Has a Global Effect on Cell Surface - Alexander Shulman (American Society for Microbiology, 2018)
ABSTRACT Many strains of Escherichia coli carry a 29,250-bp ETT2 pathogenicity island (PAI), which includes genes predicted to encode type III secretion system (T3SS) components. Because it is similar to the Salmonella pathogenicity island 1 (SPI-1) system, encoding a T3SS in Salmonella enterica, it was assumed that ETT2 also encodes a secretion system injecting effectors into host cells. This assumption was checked in E. coli serotype O2—associated with urinary tract infections and septicemia—which has an intact ETT2 gene cluster, in contrast to most strains in which this cluster carries deletions and mutations. A proteomic search did not reveal any putative secreted effector. Instead, the majority of the secreted proteins were identified as flagellar proteins. A deletion of the ETT2 gene cluster significantly reduced the secretion of flagellar proteins, resulting in reduced motility. There was also a significant reduction in the transcriptional level of flagellar genes, indicating that ETT2 affects the synthesis, rather than secretion, of flagellar proteins. The ETT2 deletion also resulted in additional major changes in secretion of fimbrial proteins and cell surface proteins, resulting in relative resistance to detergents and hydrophobic antibiotics (novobiocin), secretion of large amounts of outer membrane vesicles (OMVs), and altered multicellular behavior. Most important, the ETT2 deletion mutants were sensitive to serum. These major changes indicate that the ETT2 gene cluster has a global effect on cell surface and physiology, which is especially important for pathogenicity, as it contributes to the ability of the bacteria to survive serum and cause sepsis. IMPORTANCE Drug-resistant extraintestinal pathogenic E. coli (ExPEC) strains are major pathogens, especially in hospital- and community-acquired infections. They are the major cause of urinary tract infections and are often involved in septicemia with high mortality. ExPEC strains are characterized by broad-spectrum antibiotic resistance, and development of a vaccine is not trivial because the ExPEC strains include a large number of serotypes. It is therefore important to understand the virulence factors that are involved in pathogenicity of ExPEC and identify new targets for development of antibacterial drugs or vaccines. Such a target could be ETT2, a unique type III secretion system present (complete or in parts) in many ExPEC strains. Here, we show that this system has a major effect on the bacterial surface—it affects sensitivity to drugs, motility, and secretion of extracellular proteins and outer membrane vesicles. Most importantly, this system is important for serum resistance, a prerequisite for septicemia.